Irish and New Zealand Midwives' expertise at preserving the perineum intact (the MEPPI study): perspectives on preparations for birth - BEGLEY, CECILY; Smith, Valerie; Guilliland, Karen; Dixon, Lesley; Reilly, Mary; Keegan, Caroline; McCann, Colette (My University, 2017)
Objectives: perineal trauma during birth can result in short or long term morbidity for women. Internationally, rates of episiotomy and severe perineal tears vary considerably. In New Zealand, in 2011, and in a trial of midwife-led care in Ireland, episiotomy rates were found to be considerably lower than those in many other countries. A qualitative exploratory study was undertaken to ascertain how midwives achieve these low rates, in these countries and settings. Design and participants: a qualitative exploratory study was conducted. Midwives expert in preserving the perineum intact (PPI) from two maternity units in the Republic of Ireland and from varied birth settings in New Zealand, were eligible to participate. Twenty-one consenting midwives took part, seven from Ireland and 14 from New Zealand. Methods: university ethical approval was granted. Face-to-face, semi-structured interviews were used to collect the data. Interviews were recorded and transcribed verbatim. The data were analysed using Ethnograph software and were organised into prominent themes. Findings: four themes were identified; ‘Sources of knowledge for PPI’, ‘Associated factors’, ‘Decision-making on episiotomy’, and ‘Preparations for PPI’. Participants drew heavily on multiple sources of knowledge in building their own expertise for PPI. Physical characteristics of the perineum featured prominently as factors leading to PPI. Episiotomy was, in the main, only performed when there were signs of fetal distress. Antenatal perineal massage was supported. Conclusion: this study provides valuable insight into the views and skills of midwives, with expertise in PPI at birth, adding to the body of evidence on this topic.
PUBLISHED
Keywords: Midwives' expertise; Intact perineum; Perineal care; Perineal trauma; Episiotomy; CHILDBIRTH; Choice in Childbirth; EPISIOTOMY; Normal Childbirth; PERINEAL INJURY; PERINEAL LACERATIONS; Physiological Childbirth; intact perineum; Health